Numerical simulation of fault development in fold-and-thrust belt of Nepal Himalaya - Chamlagain, D; Hayashi, D (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 111